BEYOND THE RED PEN: EXPLORING EFL STUDENTS’ AUTONOMY AND STRUGGLES IN GRAMMAR CORRECTION - Widiyantari, Yunita; Rahma Aji, Kresna (English Education Journal, 2025)
This study investigates how Grammarly, an automated writing feedback tool, supports the development of learner autonomy in grammar correction among EFL students; uncovers students’ perceptions of Grammarly’s role in grammar correction, their self-perceived responsibility in revision, and the challenges they face in becoming autonomous writers. This qualitative case study research involved ten students from the English Education Program at UIN Walisongo Semarang, representing both fifth and seventh semesters. Data were collected through semi-structured interviews, classroom observations, and document analysis of student writing samples. The findings reveal that Grammarly contributes to learner autonomy by providing real-time, non-judgmental feedback that encourages revision and raises grammatical awareness. Students demonstrated increasing responsibility for their learning by combining Grammarly feedback with self-editing and peer consultation. However, challenges such as tool over-reliance, limited grammar knowledge, and emotional barriers were also evident. The study concludes that while Grammarly has significant potential to support grammar learning autonomy, its effectiveness depends on students’ critical engagement and reflective use. Pedagogical guidance is needed to help learners maximize the tool’s benefits and avoid passive dependence